(untitled) (Research, Society and Development, 2022)
Gynoid lipodystrophy (GL), popularly known as cellulite, affects 85% of women after puberty. The aim of the study was to develop, characterize and evaluate the effectiveness of a topical formulation based on Coffea canephora green extract (GCE) applied by phonophoresis in the treatment of GL in young women. Formulations with 1.0% (w/w) and 3.0% (w/w) of GCE were developed and characterized by organoleptic analysis, pH, centrifugation, caffeine content, rheology, spreadability, preliminary stability and cytotoxic analysis. And after the selection of the formulation, in a longitudinal, randomized and blind study, with volunteers in separate groups, the Control Group (CG, n=15) used the formulation based on a copolymer of sodium acrylates and lecithin (Lec) and the Test Group (TG, n=15) the copolymer formulation of sodium acrylates and lecithin containing 3.0% (w/w) of GCE (Lec/GCE3). Volunteers were assessed before and after treatment for cellulite severity using the Cellulite Severity Scale (CSS) and quality of life using the Dermatology Life Quality Index (DLQI-BRA). The groups were treated with 5 sessions, twice a week, 20 min/session. As a result, the GT achieved a significant reduction (p=0.002) in cellulite severity according to the CSS and both groups showed significant changes in the DLQI-BRA after treatment, CG (p=0.001) and TG (p=0.001). We conclude that the LEC/GCE3 formulation applied by phonophoresis was effective for cellulite in young women.